Multiple Infectious Agents and the Origins of Atherosclerotic Coronary Artery Disease - Lawson, James S. (Frontiers in Cardiovascular Medicine, 2016)
Although deaths due to atherosclerotic coronary artery disease (ACAD ) have fallen dramatically during the past 50 years, ACAD remains as the leading cause of death in all continents, except Africa, where deaths due to infections are still dominant . Although food and nutrition have a proven role in atherosclerosis, the underlying causes of ACAD remain unknown. This is despite a century of intensive research dominated by investigations into the saturated fat hypothesis. In this review it is hypothesised that the rise and fall in ACAD during the past 100 years is primarily due to the parallel rise and fall in the prevalence of coronary atheroma, the underlying disease. It is further hypothesised that infectious pathogens initiate atherosclerosis mainly during infancy and childhood. It is speculated that widespread use of antibiotics and vaccines against bacterial and viral infections, may be the reason for the dramatic fall in coronary atheroma and ACAD during the past 50 years. The relevant evidence and a working hypothesis are included in this review.